Therapeutic timing limitations of postnatal darbepoetin in a valproic acid rat model of Autism Spectrum Disorder - Ömer Yusuf İpek; Tuğba Kirboğa; Ercan Babur; Nurcan Dursun; Cem Süer (PLoS ONE, 2025)
Autism spectrum disorder (ASD) arises from complex genetic and environmental factors that disrupt neural development during early brain maturation. Erythropoietin (EPO) has been studied for its neuroprotective effects and more recently for its potential to influence neurodevelopment in early postnatal ASD models. However, ASD is not typically diagnosed in humans until 2–3 years of age, a stage well beyond early postnatal development. To address this timing gap, we administered darbepoetin alfa, a long-acting EPO analogue, to valproic acid-exposed rats beginning at postnatal day 21 for five consecutive days, and assessed ASD-relevant social and cognitive behaviors. Behavioral assessments using the three-chamber test and Morris Water Maze revealed no significant improvements in ASD-relevant behaviors despite clear systemic activity, as evidenced by substantial hematocrit elevation (~70%). Our findings suggest the therapeutic window for EPO analogues may close before the post-diagnostic period, highlighting a critical translational challenge: interventions effective in early neonatal windows may not retain efficacy at clinically accessible diagnostic stages. The pronounced hematological response further precludes testing whether higher doses could compensate for delayed timing, though non-erythropoietic derivatives may circumvent this limitation in future studies.